2016
DOI: 10.1007/s12017-016-8388-8
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Resilience in Stress Reduction for Caregivers of Alzheimer’s Patients

Abstract: Caregiving for a dementia patient is associated with increased risk of psychological and physical health problems. We investigated whether a mindfulness-based stress reduction (MBSR) training course for caregivers that closely models the MBSR curriculum originally established by the Center of Mindfulness at the University of Massachusetts may improve the psychological resilience of non-professional caregivers of Alzheimer's disease patients. Twenty adult non-professional caregivers of dementia patients partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…This latter is an 8-week integrated approach, an amalgam of mindfulness meditation, concentrative meditation, breathing exercises, Yoga, autogenic training, and Buddhist philosophy. Harkess et al, 2016Ren et al, 2012Chaix et al, 2017, 2020García-Campayo et al, 2018Kaliman et al, 2014Bishop et al, 2018 Differential gene expression (Pathways affected) Qu et al, 2013;Bower et al, 2014Irwin et al, 2014Kinney et al, 2019Li et al, 2005Sharma et al, 2008Kumar and Balkrishna, 2009;Black et al, 2013Creswell et al, 2012Ho et al, 2016 Biomolecules Dada et al, 2015;Mohammad et al, 2019Campo et al, 2015Ryu et al, 1996Lee et al, 2004 Reviewed in: Daube and Jakobsche, 2015 Kasala et al, 2014 Reviewed in Black and Slavich, 2016 Reviewed in Black and Slavich, 2016 Neurotrophins Naveen et al, 2013Naveen et al, , 2016Cahn et al, 2017;Tolahunase et al, 2017L Saliva Ben-Soussan et al, 2015bVenditti et al, 2015;Caserta et al, 2019CS, L Saliva, Serum Pan et al, 2006 (SK/KK) Balasubramanian et al, 2015 (Pranayama) CS Serum Dada et al, 2018;Gagrani et al, 2018 MBSR Interventions (MBI;…”
Section: Effects Of Multiple-meditation Protocols: Mindfulness-based mentioning
confidence: 99%
“…This latter is an 8-week integrated approach, an amalgam of mindfulness meditation, concentrative meditation, breathing exercises, Yoga, autogenic training, and Buddhist philosophy. Harkess et al, 2016Ren et al, 2012Chaix et al, 2017, 2020García-Campayo et al, 2018Kaliman et al, 2014Bishop et al, 2018 Differential gene expression (Pathways affected) Qu et al, 2013;Bower et al, 2014Irwin et al, 2014Kinney et al, 2019Li et al, 2005Sharma et al, 2008Kumar and Balkrishna, 2009;Black et al, 2013Creswell et al, 2012Ho et al, 2016 Biomolecules Dada et al, 2015;Mohammad et al, 2019Campo et al, 2015Ryu et al, 1996Lee et al, 2004 Reviewed in: Daube and Jakobsche, 2015 Kasala et al, 2014 Reviewed in Black and Slavich, 2016 Reviewed in Black and Slavich, 2016 Neurotrophins Naveen et al, 2013Naveen et al, , 2016Cahn et al, 2017;Tolahunase et al, 2017L Saliva Ben-Soussan et al, 2015bVenditti et al, 2015;Caserta et al, 2019CS, L Saliva, Serum Pan et al, 2006 (SK/KK) Balasubramanian et al, 2015 (Pranayama) CS Serum Dada et al, 2018;Gagrani et al, 2018 MBSR Interventions (MBI;…”
Section: Effects Of Multiple-meditation Protocols: Mindfulness-based mentioning
confidence: 99%
“…Ho and colleagues (39) chose a sample of caregivers, a chronically stressed population, to test the effects of MBSR. The intervention was slightly modified by shortening the length of weekly classes from regular 2.5 to 1.5 h to meet the demanding daily schedules of caregivers, but the content remained the same.…”
Section: Summary Of Studies On Mbis Using Gene Expression Analysismentioning
confidence: 99%
“…These mechanisms are the focus of the present review. Literature has linked these biological markers to PTSD prognosis (Castro-Vale, van Rossum, Machado, Mota-Cardoso, & Carvalho, 2016) and shown that psychotherapy and epigenetic drugs such as methyltransferases can influence gene expression and psychiatric symptoms (e.g., Ho et al, 2016;Peedicayil, 2011).…”
mentioning
confidence: 99%